Highly efficient ZnO-based dye-sensitized solar cells with low-cost Co–Ni/carbon aerogel composites as counter electrodes. (14th September 2018) - Cheng, Jian; Ma, Junhong; Ma, Yuhua; Zhou, Cui; Qiang, Yue; Zhou, Xiaofeng; Yang, Jianya; Shi, Haokun; Xie, Yahong
Abstract : Low-cost materials fabricated high-performance Co–Ni/carbon aerogels as counter electrodes. Abstract : Dye-sensitized solar cells (DSSCs) have many advantages, but the use of expensive platinum counter electrodes (CEs) limits their industrial applications. In this work, a Co–Ni/carbon aerogel composite with a unique three-dimensional network structure and high specific surface area was prepared through simple ion exchange and carbonization of low-cost sodium alginate supramolecular hydrogels. Using this metal/carbon aerogel composite as the CE (hereafter denoted as CAE) of ZnO-based DSSCs, a photoelectric conversion efficiency (PCE) of 5.08% was obtained. This value was 94.44% of the PCE obtained using Pt. Analysis of current–voltage curves, cyclic voltammograms, and electrochemical impedance spectra revealed that the fabricated CAE had higher catalytic activity than a Pt CE and comparable charge-transfer ability. The adhesion of the CAE onto FTO was also strong with carbon paste as an adhesive.